Baicalein Induces Mitochondrial Autophagy to Prevent Parkinson's Disease in Rats via miR-30b and the SIRT1/AMPK/mTOR Pathway - Chen, Min; Peng, Li; Gong, Ping; Zheng, Xiaoli; Sun, Tao; Zhang, Xiaoqiao; Huo, Jiangtao (Frontiers in Neurology, 2022)
Parkinson's disease (PD) is a prevailing neurodegenerative disorder. Baicalein has neuroprotective effects on PD animals, but its mechanism isn’t clarified. We explored baicalein effects on PD rats. PD rat models were established by injecting 6-hydroxydopamine into the striatum of substantia nigra on the left side of the rat brain and treated with baicalein. Dopamine (DA) content, neuronal apoptosis, neuronal injury, neuronal mitochondria, and autophagy were assessed. Baicalein-treated PD rats were treated with autophagy inhibitor 3-methyladenine to identify the role of autophagy in PD. PD rats were injected with AgomiR-30b-5p or sh-SIRT1 plasmids and treated with baicalein. PD rats elicited decreased neurological score and DA secretion of the striatum, increased neuronal apoptosis, and injury, and reduced number of mitochondria and autophagy, while baicalein alleviated neuronal injury and partly recovered mitochondrial dysfunction, but 3-methyladenine inhibited the protection of baicalein. miR-30b-5p was elevated and SIRT1 was diminished in PD rats and inhibited by baicalein. miR-30b-5p targeted SIRT1. miR-30b-5p overexpression or SIRT1 silencing annulled the protection of baicalein. The phosphorylation level of AMPK in the substantia nigra of PD rats was decreased and mTOR was increased, while baicalein annulled these trends. Briefly, baicalein activated mitochondrial autophagy via miR-30b-5p and the SIRT1/AMPK/mTOR pathway, thus protecting PD rats.